Applying the Water-Energy-Food Nexus to the Charcoal Value Chain - Hoffmann, Harry K.; Sander, Klas; Brüntrup, Michael; Sieber, Stefan (Frontiers in Environmental Science, 2017)
Globally, natural resources are increasingly under pressure, especially due to population growth, economic growth and transformation as well as climate change. As a result, the water, energy and food (WEF) nexus approach has emerged to understand interdependencies and commonly manage resources within a multi-scale and multi-level framework. In Sub-Saharan Africa, the high and growing consumption of traditional biomass for cooking purposes - notably fuelwood and charcoal - is both a key source of energy and contributor for food security as well as a pressure on natural resources. Improving the bioenergy value chains is essential for limiting environmental degradation and for securing the livelihoods of millions of people. Although the WEF nexus approach entails large potential to address the complex problems arising along the bioenergy value chains, these are currently not considered. Based on the WEF nexus approach, we analyze the different steps within the charcoal value chain in Sub-Saharan Africa and highlight the respective interdependencies and the potential for improving overall socio-economic and environmental sustainability. We emphasize the water, energy and food related implications of vicious and virtuous production cycles, separated by value chain segments. We discuss the potential and major challenges for implementing more sustainable value chains. Furthermore, we underline the necessity of applying WEF nexus approaches to these value chains in order to optimize environmental and social outcomes.